Analisis Kepuasan Kerja,Budaya Organisasi,Turnover Intention dan Kinerja Karyawan Perusahaan Asuransi - Prasetya, Wibawa; Aryantoro, Gregorius Wisnu (Metris: Jurnal Sains dan Teknologi, 2021)
This research is a type of survey research that aims to analyze job satisfaction, organizational culture, turnover intention and performance of employees of insurance companies. In addition, to examine the effect of job satisfaction and organizational culture on the level of turnover intention and employee performance. The research method used is a quantitative method. Data collection using a questionnaire that has been tested for validity and reliability. The sample in this study amounted to 170 respondents taken from an unknown population The sampling technique was used purposive sampling. The data obtained is calculated the average value per research variable. To determine the effect between variables, the data were processed and analyzed using the Structural Equation Modeling (SEM) method with LISREL 8.80 software. The results of the research show that job satisfaction has an effect on turnover intention, organizational culture has an effect on turnover intention, job satisfaction has an effect on employee performance, while organizational culture has no effect on employee performance and turnover intention has no effect on employee performance. The average value of job satisfaction is 3.92, which means that employees are satisfied with the work itself, salary, co-workers, existing promotions. The average value of organizational culture is 4.07, which means that employees feel the freedom to express opinions, a good company environment and employee involvement in completing work. The average value of Turnover Intention is 1.89, meaning that the employee's desire to move, absenteeism and violation of regulations is high. The average value for performance is 4.21, which means that the quantity, quality and use of time in completing the work are very good.